BS ISO/IEC 23488. Information technology. Computer graphics, image processing and environment data representation. Object/Environmental Representation for Image based Rendering in Virtual/Mixed and Augmented Reality (VR/MAR). (31st August 2021) - British Standards Institution,
No abstract available